(untitled) (Boletin Médico de Postgrado, 2024)
Since ancient times, women have suffered a myriad of setbacks, discrimination, and injustice. In the first social settlements, based on the physical build of people, a division of labor was established that led women to take care of the tasks centered on the care of the home and family, which has been culturally transmitted to the present day. However, during long historical periods, significant struggles of women have taken place in different areas of life, which has transformed society to adapt to the rights demanded in favor of equality, equity, and justice. This is why, in the last fifty years, different governments and civil society organizations have strived to formulate and implement policies capable of creating fairer and more balanced conditions for women and men. In this sense, this research aimed to reveal the epistemic social reality about gender equality in the labor sphere of the Judicial Circuit in Matters of Crimes of Violence against Women, in the city of Barquisimeto, state of Lara. For this, it was required to interpret the conceptual heritage of gender equality in social actors, understand the characteristics that make up the environment, and reflect on their perceptions in relation to gender equality in their work environment, within a qualitative paradigm, nourished by the feminist approach, with ethnographic method, to make a hermeneutics of the beliefs, perceptions, impressions, and experiences of the reality of the women who coexist there.